Individualism and Collectivism in International Community During Covid19 Pandemic 2020 - Tendy, Tendy (Interdependence Journal of International Studies, 2022)
Covid19 pandemic has changed the face of the world depicted in people to people relations, both domestically and internationally. Throughout the year of 2020, we have become familiar with some of the very popular terminologies for instance the word lockdown, social distancing, work from home, and the infamous names of Ken and Karen. These terminologies mark the shifts on how people conduct their interpersonal interactions, as the consequences of full-scale implementation of health protocols. This article will discuss the situation of individualism and collectivism as an existence within people to people interactions. It is known that both conceptions